Clonación e ICSI interespecífica en felinos y reprogramación nuclear - Moro, Lucía N. (2015)
The extinction of animals is one of the most alarming consequences caused by environmental degradation, and deprives us of unique genetic materials. The Felidae family does not scape to this problem and it is for this reason that reproductive biotechnologies become very usefull tools for the conservation of these species. The hypothesis of this doctoral thesis suggests that it is possible to use domestic cat oocytes or ooplasts to develop reproductive techniques applicable to wild felids. Thus, our principal objective was to adapt the existing biotechnologies to reproduce and preserve endangered felid species. Due to the limited availability of oocytes from wild cats, domestic cat oocytes (Dc) were used as an experimental model to develop different reproductive techniques. In Chapter I, different conditions of maturation and embryo culture were studied to improve the intracytoplasmic sperm injection (ICSI) technique in the Dc. Thus, we determined that by using the insulin-transferrin and selenium supplement (ITS) during maturation of the oocytes and low oxygen tension (5%O2) during embryo culture, higher rates of blastocyst formation were obtained. These conditions were chosen to generate interspecific embryos by injecting cheetah (Ch, Acinonyx jubatus) and leopard (Leo, Panthera pardus) spermatozoa in Dc oocytes. In this experiment, we obtained similar blastocyst rates in both the Dc homoespecífic ICSI and the interspecific ICSI, without the need of chemical activation after sperm injection. This work was useful to evaluate the developmental ability of wild cat sperm by the interspecific ICSI technique, using Dc oocytes.\nIn Chapter II, the somatic cell nuclear transfer (SCNT) was studied in felids. The aim was to develop new strategies to improve this technique in the Dc and wild felids. Firstly, we evaluated three different SCNT techniques in the Dc, two of which had not been previously reported in this species. The three techniques were: fusion of the donor cell to an ooplast with zona pellucida (ZP), injection of the donor cell in an ooplast with ZP, and fusion of the donor cell to an ooplasts ZP free. The latter one was the most efficient, so we decided to use this technique to determine the ability of Dc ooplasts to reprogram phylogenetically distant feline cells by interspecific SCNT (iSCNT). The donor cells used were from bengal cat (Be, an hybrid between Dc and asian leopard), cheetah or tiger (Ti, Panthera tigris). The effect of embryo aggregation was also assessed by culturing ZP free reconstructed embryos in microwells, individually (1X), or 2 clones of the same species toghether (2X, aggregated embryos), in order to improve the in vitro development and the quality of the embryos, as had been previously reported for other species. In this experiment, we obtained embryos until the blastocyst stage of all the groups. Aggregation improved embryonic development in all the species and the quality of Ti2X and Gd2X blastocysts. Furthermore, the relative expression of genes related to pluripotency and early differentiation (OCT4, NANOG, SOX2 and CDX2) was studied in Dc, Be and Ch clone blastocysts. This analysis found that cat embryos had higher relative expression level of the four genes compared to the in vitro fertilized embryos (IVF, control group). However, this overexpression was reduced in Dc2X blastocysts reaching similar relative levels of gene expression as those of the IVF control. Moreover, the relative expression level of the four genes in cheetah embryos were lower tan the control, obtaining the same result for the relative expression level of OCT4 in bengal embryos.\nIn conclusion, the ICSI technique represents a method directly applicable to wild felids reproduction, especially when semen samples are of poor quality. With respect to SCNT and iSCNT, cat oocytes were able to reprogram wild felid cells and to generate blastocysts. Furthermore, clone aggregation has shown to improve embryo development in all the groups and to normalize the relative gene expression only in the Dc but not in interspecific embryos. The SCNT is an alternative technique to generate animals that are not in good reproductive conditions or that have died and their cells were cryopreserved. This thesis provides new knowledge to biotechnological methodologies and reproduction in felids.